Annotation and overview of the Pseudomonas savastanoi pv. savastanoi NCPPB 3335 draft genome reveals the virulence gene complement of a tumour‐inducing pathogen of woody hosts - Pablo Rodríguez‐Palenzuela; Isabel M. Matas; Jesús Murillo; Emilia López‐Solanilla; Leire Bardaji; Isabel Pérez‐Martínez; Martín E. Rodríguez‐Moskera; Ramón Penyalver; Maria M. López; José M. Quesada; Bryan S. Biehl; Nicole T. Perna; et al. (Environmental Microbiology, 2010)
Summary Pseudomonas savastanoi pv. savastanoi is a tumour‐inducing pathogen of Olea europaea L. causing olive knot disease. Bioinformatic analysis of the draft genome sequence of strain NCPPB 3335, which encodes 5232 predicted coding genes on a total length of 5856 998 bp and a 57.12% G + C, revealed a large degree of conservation with Pseudomonas syringae pv. phaseolicola 1448A and P. syringae pv. tabaci 11528. However, NCPPB 3335 contains twelve variable genomic regions, which are absent in all previously sequenced P. syringae strains. Various features that could contribute to the ability of this strain to survive in a woody host were identified, including broad catabolic and transport capabilities for degrading plant‐derived aromatic compounds, the duplication of sequences related to the biosynthesis of the phytohormone indoleacetic acid ( iaaM, iaaH ) and its amino acid conjugate indoleacetic acid‐lysine ( iaaL gene), and the repertoire of strain‐specific putative type III secretion system effectors. Access to this seventh genome sequence belonging to the ‘ P. syringae complex’ allowed us to identify 73 predicted coding genes that are NCPPB 3335‐specific. Results shown here provide the basis for detailed functional analysis of a tumour‐inducing pathogen of woody hosts and for the study of specific adaptations of a P. savastanoi pathovar.